180k views
1 vote
What is the rule for the reflection?

A. ry=x(x, y) → (–y, –x)
B. ry=–x(x, y) → (–y, –x)
C. ry=x(x, y) → (y, x)
D. ry=–x(x, y) → (y, x)

What is the rule for the reflection? A. ry=x(x, y) → (–y, –x) B. ry=–x(x, y) → (–y-example-1
User Drakalex
by
5.8k points

2 Answers

4 votes
The answer is C because if you put

x = - 2 \\ y = 1 \\
Find the reflected two points which are:

x = 1 \\ y = - 2
They're just flipped equations
User Balaji Venkatraman
by
6.2k points
6 votes

Answer: C. ry=x(x, y) → (y, x)

Explanation:

From the given picture, the coordinates of A = (-2,1), B(3,4) and C(-4,1)

and the coordinates of A' =(1,-2), B'(4,3) and C'(1,-4)

We can see that the x and y coordinates of ΔABC has changed their place in ΔA'B'C'.

Therefore, the rule for the given reflection is in option C.

i.e. ry=x(x, y) → (y, x) .

User BatyrCan
by
6.1k points